2010
DOI: 10.1161/circresaha.109.196030
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modification of Mesenchymal Stem Cells Overexpressing CCR1 Increases Cell Viability, Migration, Engraftment, and Capillary Density in the Injured Myocardium

Abstract: Rationale: Although mesenchymal stem cell (MSC) transplantation has been shown to promote cardiac repair in acute myocardial injury in vivo, its overall restorative capacity appears to be restricted mainly because of poor cell viability and low engraftment in the ischemic myocardium. Specific chemokines are upregulated in the infarcted myocardium. However the expression levels of the corresponding chemokine receptors (eg, CCR1, CXCR2) in MSCs are very low. We hypothesized that this discordance may account for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(167 citation statements)
references
References 24 publications
3
162
0
2
Order By: Relevance
“…Few studies have been conducted focusing on this chemokine, which has already been shown to attract MSC in migration assays as well as induced MI models (23). Furthermore, genetic modification of MSC with the CCR1 gene (CCL7 receptor) was shown to increase the viability, recruitment and retention of those cells in the MI regenerative niche (24). Plasma levels of CCL7, however, were not increased in MI patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been conducted focusing on this chemokine, which has already been shown to attract MSC in migration assays as well as induced MI models (23). Furthermore, genetic modification of MSC with the CCR1 gene (CCL7 receptor) was shown to increase the viability, recruitment and retention of those cells in the MI regenerative niche (24). Plasma levels of CCL7, however, were not increased in MI patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects observed on heart function, remodelling, and infarct size could have been due to increased secretion of vascular endothelial growth factor and decreased interleukin 6 levels in hearts of animals treated with genetically modified cells. Mesenchymal stem cells have also been used to overexpress the chemokine receptors CCR1 and CXCR2 before intramyocardial injection into infarcted heart (Huang et al, 2010). Stem cells with overexpression of CCR1 had increased survival intramyocardially, which was accompanied by less cardiac remodelling, increased capillarization, and improved cardiac function in both acute and chronic (4 weeks) observation times.…”
Section: Genetically Engineered Stem Cells As Cardioprotective Agentsmentioning
confidence: 99%
“…We therefore hypothesized that the use of bone marrow derived mesenchymal stem cells might be a better option. Mesenchymal stem cells have been extensively studied for their cardiac reparability and regenerative potential Kim et al 2010.;Labovsky et al 2010;Haider et al 2009) besides having superior transgene carrying capability Huang et al 2010;Tang et al 2010;Haider et al 2008). Besides, we also opted to replace Vegf with survival signaling molecule Akt to support survival of the genetically modified mesenchymal stem cells (Jiang et al 2006).…”
Section: Combining Stem Cell Transplantation and Angiopoietin-1 Deliverymentioning
confidence: 99%